Balinese Script’s Character Reconstruction Using Linear Discriminant Analysis - Made Sudarma; Sri Ariyani; Manuh Artana (Institute of Advanced Engineering and Science, 2016)
Balinese people have one of the civilization history and cultural heritage are handwritten in Balinese script on palm leaves known as Balinese Papyrus (LontarAksara Bali). Until now that cultural heritage is still continuously strived its preservation along with the implementation begin to be abandoned in public life. Some of Balinese Papyrus now begin to rot and fade under influenced by age. Information technology utilization can be a tool to solve the problems faced in the preservation of the Balinese papyrus. By using digital image processing techniques, the papyrus script can be reconstructed digitally so that it can be retrieved and store the content in the digital media. Balinese papyrus reconstructed through several processes from scanning into a digital image, performing preprocessing for image quality improvement, segmenting the Balinese characters on image, doing character recognition using LDA algorithm, rearranging the result of recognition in accordance with the original content in papyrus, and translating that characters result into Latin. LDA algorithm quite successfully performs the classification associated with handwritten character recognition.